2013
DOI: 10.1088/0004-6256/146/4/94
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Rr Lyrae Stars in Segue 2 and Segue 3

Abstract: We present an extensive search for RR Lyrae stars in and around the ultra-faint Milky Way companions Segue 2 and Segue 3. The former (M V = −2.5, Belokurov et al. 2009) appears to be an extremely faint dwarf galaxy companion of the Milky Way. The latter (M V = 0.0, Fadely et al. 2011)is among the faintest star clusters known. We use B and V band time-series imaging obtained at the WIYN 0.9 meter telescope at Kitt Peak National Observatory to search for RR Lyrae in these objects. In our Segue 2 observations, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 62 publications
3
31
0
Order By: Relevance
“…This approach will not be appropriate for very small UFDs, where fewer than three RR Lyrae stars may be present (e.g., Musella et al 2009;Dall'Ora et al 2012;Boettcher et al 2013, for Ursa Major II, Coma Berenices, and Segue 2 and Segue 3, respectively), or UFDs closer to the Galactic center where the field density of RR Lyrae stars is significant. But for distant Milky Way satellites, this approach seems promising.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach will not be appropriate for very small UFDs, where fewer than three RR Lyrae stars may be present (e.g., Musella et al 2009;Dall'Ora et al 2012;Boettcher et al 2013, for Ursa Major II, Coma Berenices, and Segue 2 and Segue 3, respectively), or UFDs closer to the Galactic center where the field density of RR Lyrae stars is significant. But for distant Milky Way satellites, this approach seems promising.…”
Section: Resultsmentioning
confidence: 99%
“…We used the general form of the maximum likelihood technique from Boettcher et al (2013) to calibrate our data to SDSS without spatial correction terms, as there are no residual trends in pixel position for the DECam or 90Prime instruments. We determined uncertainties on the zeropoints and colorterms by performing a 1000 iteration bootstrap and added these in quadrature to the photometric uncertainties returned by allstar.…”
Section: Photometry and Calibrationmentioning
confidence: 99%
“…Belokurov et al (2009) presented MMT/Hectochelle spectroscopy of Segue 2 in the discovery paper for the system, which Kirby et al (2013a) supplemented with a large Keck/DEIMOS data set. Imaging of Segue 2 by Boettcher et al (2013) revealed 1 RR Lyrae variable, which was also identified spectroscopically by Kirby et al (2013a). Roederer & Kirby (2014) analyzed the chemical abundance pattern of the brightest RGB member found by Kirby et al (2013a) with a high-resolution Magellan/MIKE spectrum.…”
Section: Appendixmentioning
confidence: 94%
“…Since 2006, about 13 UFDs (with M V > −7) have been reported to contain RR Lyrae variables (Vivas et al 2016, see their Table 4 for a recent compilation), including Boötes I (holding the current record with 15 RR Lyrae stars) and Segue I, one of the faintest UFDs known (Simon et al 2011). It is interesting to note that all dwarf galaxies searched for variable stars so far have at least one RR Lyrae star (Vivas et al 2016; see also Garofalo et al 2013;Boettcher et al 2013;Sesar et al 2014;Medina et al 2017) regardless of the total luminosity.…”
Section: Introductionmentioning
confidence: 99%